Tactile comics, disability studies and the mind's eye: on "A Boat Tour" (2017) in Venice with Max. Issue 5 (3rd September 2021) - Fraser, Benjamin
ABSTRACT: Positioned at the intersection of disability studies and urban comics studies, this article explores the artistic form, content and social engagement of the tactile comic 'A Boat Tour'. Though the comic's credited author is Max (a.k.a. Francesc Capdevila Gisbert; Barcelona, 1956-), it was nonetheless developed through a collaborative process as part of the Catalan contribution to La Biennale di Venezia. Using both braille and a form of haut-relief braille-like texture, the comics sensory representation of a boat tour experience is significant on two levels: first for its contributions to a transnational disability culture and its general avoidance of the problems common in disability representation; and second for its innovations within the tactile comics form. These innovations are explored in the context of scholarship on the Iberian comic, the wordless and tactile comic, and accounts of visual impairment understood as a social construction. In particular, the work of Georgina Kleege, including her recent book More than Meets the Eye, demonstrates that the distance routinely established between visual art and the experience of visual impairment is itself an ableist construction.